Pengaruh Desain Visual Konten Singkat Cerita terhadap Peningkatan Engagement Akun Instagram @Sukabumi_ - Rizka Arivia Putri; David Rizar Nugroho; Enden Darjatul Ulya; Mulyono Mulyono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study analyzes the influence of visual design in short-story content on the Engagement level of the @sukabumi_ community Instagram account. A quantitative approach was employed, utilizing an online Likert-scale questionnaire distributed to 100 active Instagram users aged 17–30 years. Data were analyzed through average score tabulation and a simple linear regression using SPSS. The findings reveal that all visual design indicators—color, typography, layout, and images—were rated very highly, indicating the visual elements on @sukabumi_ content are both aesthetically and communicatively effective. Engagement indicators such as Likes, Comments, Shares, and Saves were also rated highly, with the ‘Save’ action prevailing as the most common response due to the perceived relevance and value of the content. Regression analysis confirmed that visual design has a positive and significant effect on Engagement , contributing 40.8% to the variation in user interactions. These results underscore the importance of consistent and audience-appropriate visual design strategies to enhance communication effectiveness and increase user Engagement within local digital communities.